LANGUAGE STYLE IN ADVERTISEMENT SLOGAN ON INSTAGRAM (Karya Ilmiah Mahasiswa (KIMA), 2024)
This study aims to find out the types of language style contained in the beauty product advertising slogan in Instagram. The research method was collects samples of beauty product advertising slogans from several Instagram accounts using the read and note technique. The research data was in the form of slogans on beauty advertisements uploaded on several beauty product Instagram account pages. The data were analyzed by reading the data that had been found in observing advertisements on Instagram. The result of the study was 18 advertising slogan data containing 28 language styles. The results of the analysis consist of 8 metaphors, 7 alliterations, 4 hyperboles, 2 anaphor, 3 antitheses, 1 personification, I simile, I allusion, and 1 euphemism.